Human Value-Oriented Management: A Meta-Synthesis of Contributions by Professor S. K. Chakraborty. (January 2023) - Kar, Subhasree; Tripathi, Shiv; Sahoo, Deepak Kumar
The role of Indian ethos in management practices is explored by several management scholars and practitioners. Professor Sitangshu Kumar Chakraborty (popularly known as Professor S. K. Chakraborty, hereinafter referred to as SKC in this article) is one of the pioneering scholars of human value-oriented management practices and has made significant contributions in linking the management knowledge and practices to classical Indian ethos and Vedantic wisdom. In today's technologically advanced and economically fast-paced world, there is a rising concern about falling human values in work and in personal life, which must be addressed to understand the deeper meaning of work and a higher purpose in life. SKC's innovative approaches to human values in management education for practising managers are quite significant in this regard. This article is a sincere attempt to explore and synthesize the contributions of SKC to the human value-oriented management that evolved around the fundamental pillars of classical Indian ethos and Vedantic wisdom and the implication of those values for today's managers to realign their managerial practices. This article is based on a bibliometric analysis of published articles drawn from secondary sources and is a tribute to the life and legacy of SKC on human value-based management.